2020
DOI: 10.1039/d0nr02172e
|View full text |Cite
|
Sign up to set email alerts
|

Efficient sub-15 nm cubic-phase core/shell upconversion nanoparticles as reporters for ensemble and single particle studies

Abstract: A set of sub-15 nm ytterbium-enriched α-NaYbF4:Er3+@CaF2 core/shell upconversion nanoparticles have been developed for both ensemble- and single particle-level imaging studies, presenting a high quantum yield of 0.77% at a low saturation power density of 110 W cm−2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Also, previously reported cubic UC-host matrices such as α-NaYF 4 , CaF 2 , SrF 2 , and α-NaYbF 4 exhibit a strong red emission. 19,23,35,[50][51][52] Moreover, the evolution of the 855 nm and 806 nm bands upon increasing χ Yb differ from the behaviour commonly observed for hexagonal β-NaYF 4 UCNC. High amounts of Yb 3+ are known to elevate surface quenching, i.e., the migration of the excitation energy to quenching sites at the surface via multiple Yb 3+ -ions.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Also, previously reported cubic UC-host matrices such as α-NaYF 4 , CaF 2 , SrF 2 , and α-NaYbF 4 exhibit a strong red emission. 19,23,35,[50][51][52] Moreover, the evolution of the 855 nm and 806 nm bands upon increasing χ Yb differ from the behaviour commonly observed for hexagonal β-NaYF 4 UCNC. High amounts of Yb 3+ are known to elevate surface quenching, i.e., the migration of the excitation energy to quenching sites at the surface via multiple Yb 3+ -ions.…”
Section: Resultsmentioning
confidence: 70%
“…Also, previously reported cubic UC-host matrices such as α-NaYF 4 , CaF 2 , SrF 2 , and α-NaYbF 4 exhibit a strong red emission. 19,23,35,50–52…”
Section: Resultsmentioning
confidence: 99%
“…Guo et al 39 demonstrated that enhanced emission intensity in GdVO 4 :Yb/Er nanoparticles doped with Lu 3+ , Y 3+ and PO 4 3− ions was realized by 980 & 1550 nm excitation. However, TSTF UCNPs often surfer from low luminescent efficiency [42][43][44] , attributing to the concentration quenching and surface defects [45][46][47][48][49][50] , which partly restrict the further applications in 3-D display. For enhancing UCL efficiency, many approaches, such as doping sensitizer, fabricating core/shell structures, changing the hosts are widely studied [51][52][53][54] .…”
Section: Introductionmentioning
confidence: 99%
“…Many excellent studies on TSTF UCNPs have been reported. [42][43][44] attributed to concentration quenching and surface defects, [45][46][47][48][49][50] which partly restrict further applications in the 3-D display. To enhance UCL efficiency, many approaches, such as doping sensitizers, fabricating core/shell structures, and changing the hosts, have been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, the higher spatial-resolution requirements of the measurements in semiconductors and biological cells demand investigation at a single-particle level. The major challenge while carrying out single-particle emission measurements is the requirement of 10 5 –10 6 W cm –2 excitation intensity as compared to 1–100 W cm –2 for bulk or ensemble samples. Recently, it has been demonstrated that core–shell architectures can lower the excitation intensity required for single-particle emission. Optical arresting, wherein the gradient force created via focusing a Gaussian laser excitation beam through a high numerical aperture microscope objective balances the photon scattering force along the light propagation direction, is an ideal noncontact approach to optically arrest single upconversion particles for further studies. , The mechanism and potential of the technique have already been demonstrated in the case of nanoparticles (quantum dots, metallic nanoparticles, upconversion particles), biological cells, bacteria, etc. The investigation of optically trapped particles facilitates the understanding of physical phenomena at a single-particle level and allows the development of efficient optical single-particle probes. ,, This single-particle spectrometry is expected to provide microstructure-dependent spectroscopic characteristics compared to ensemble studies. …”
Section: Introductionmentioning
confidence: 99%